Faktor-Faktor Yang Mempengaruhi Earning Response Coefficient (Erc) Dengan Profitabilitas Sebagai Prediktor - Delvina Hartanto, Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
Earnings information is the most responded information by investors because it provides a description of the company’s performance, but the information alone is sometimes not enough profit to serve as the basis of decision making for investors. The level of profit can be measure by using Earning Response Coefficient (ERC). The strong market reaction to earnings information reflected in the high earnings response coefficients. The purpose of this study is to analyze the effects of Firm Size and Growth with Profitability as predictor to Earning Response Coefficient. Population in this study are mining companies listed in Indonesia Stock Exchange 2014-2017. Sampling technique that used in this study is purposive sampling and obtained 14 mining companies with four years study period and give 56 sample unit. Data analysis method in this study is panel data regression using software Eviews version 10. The result showed that Firm Size and Growth has no significant effect to Earning Response Coefficient, while Profitability has negative significant effect to Earning Response Coefficient, and also Profitability strengthen the relationships of Firm Size and Growth to Earning Response Coefficient.